Requirement of Drosophila NF1 for activation of adenylyl cyclase by PACAP38-like neuropeptides. - Guo, H.F.; The, I.; Hannan, F.; Bernards, A.; Zhong, Y. (Science, 1997)
The human neurofibromatosis type 1 (NF1) tumor suppressor protein functions as a Ras-specific guanosine triphosphatase-activating protein, but the identity of Ras- mediated pathways modulated by NF1 remains unknown. A study of Drosophila NF1 mutants revealed that NF1 is essential for the cellular response to the neuropeptide PACAP38 (pituitary adenylyl cyclase-activating polypeptide) at the neuromuscular junction. The peptide induced a 100-fold enhancement of potassium currents by activating the Ras-Raf and adenylyl cyclase-adenosine 3',5'-monophosphate (cAMP) pathways. This response was eliminated in NF1 mutants. NF1 appears to regulate the rutabaga-encoded adenylyl cyclase rather than the Ras-Raf pathway. Moreover, the NF1 defect was rescued by the exposure of cells to pharmacological treatment that increased concentrations of cAMP.